OVERVIEW OF THE COMPANY’S FINANCIAL STRUCTURE - VIORICA MIRELA STEFAN-DUICU (Challenges of the Knowledge Society)
The purpose of the paper is to highlight the fact that the company’s financial structure is, empirically speaking, the parent entity from which starts all the activities that generate the self existence of the company. The company’s financial structure also known as the company’s capital structure conducts directly the organizational and inter-organizational behavior and indirectly the classification on the market of the referred economic agents. This paper aims to describe the factors that influence the company’s financial activity, it’s direct and related sources of funding used to maintain or increase a satisfying turnover and the theories that conduct the company’s capital structure.